Une recherche-action en pédagogie de l'alternance : une autre façon de se trans-former - Christine Poplimont (Presses universitaires de la Méditerranée, 2011)
The research presented here aims to understand how trainers in work/study alternation succeed or not to integrate the basics of a trainers training structured on learning processes implemented in alternation didactics, through a design which set themselves in a situation of work/study alternation. This pedagogical approach aims to get out of the traditional teaching scheme which consists in fixing the learner as a knowledge consumer. To learn means, in this case, to save knowledge. We are here with subjects able to quote lessons but which are not at all prepared to link the learning they have received and their implementation. On the contrary, the work/study alternation allows continuous shifts between experience stories and theoretical elements as well as to experience new practices. This provoked distance between posture and practice is favored by a written production, a « production of knowledge » as said by G. Lerbert (1984), which is in the University the writing of a thesis Observation fields are two groups of students in 2nd year of Master in the Provence University who must write a report. In fact, the learner must, through this written production, create links between seemingly opposed poles and ideas. From this alternation didactics may come a more global vision allowing to understand a degree of complexity susceptible to favor critical thinking.